2019
DOI: 10.1002/anie.201909706
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Dependent Photodynamic Therapy for Multiple Targets: A Highly Efficient AIE‐Active Photosensitizer for Selective Bacterial Elimination and Cancer Cell Ablation

Abstract: Pathogen infections and cancer are two major human health problems. Herein, we report the synthesis of an organic salt photosensitizer (PS), called 4TPA‐BQ, by a one‐step reaction. 4TPA‐BQ presents aggregation‐induced emission features. Owing to the aggregation‐induced reactive oxygen species generated and a sufficiently small ΔEST, 4TPA‐BQ shows a satisfactorily high 1O2 generation efficiency of 97.8 %. In vitro and in vivo experiments confirmed that 4TPA‐BQ exhibited potent photodynamic antibacterial perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
113
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(115 citation statements)
references
References 57 publications
1
113
0
1
Order By: Relevance
“…Targeted drug delivery accelerates the emergence of new AIE theranostic options. By taking advantage of bacteria-piloting agents (e.g., cationic groups, peptides, monoclonal antibodies), these "light-up" photosensitizers can be tailed with selective labeling, distinguishing, and killing of bacteria [73][74][75]. For example, the AIE photosensitizer after conjugation with positively charged zinc(II)dipicolylamine could specifically target to the negatively charged bacterial membrane via electrostatic interaction, but not to mammalian cells [76].…”
Section: Aie Photosensitizers For Bacterial Targetingmentioning
confidence: 99%
“…Targeted drug delivery accelerates the emergence of new AIE theranostic options. By taking advantage of bacteria-piloting agents (e.g., cationic groups, peptides, monoclonal antibodies), these "light-up" photosensitizers can be tailed with selective labeling, distinguishing, and killing of bacteria [73][74][75]. For example, the AIE photosensitizer after conjugation with positively charged zinc(II)dipicolylamine could specifically target to the negatively charged bacterial membrane via electrostatic interaction, but not to mammalian cells [76].…”
Section: Aie Photosensitizers For Bacterial Targetingmentioning
confidence: 99%
“…As shown in Scheme S1, o-TPBQ was readily achieved via a facile one-step synthetic route according to the previously reported literature. 46,47 Detailed experimental procedures were provided in the Supporting Information. The structure of o-TPBQ was well characterized and confirmed by NMR and high-resolution mass spectroscopies ( Figure S1-S3).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, 5L + interactions together with the multiple inter-and intra-molecular interactions (including hydrogen bonding and short contact interactions) account for AIE characteristics of o-TPBQ and c 5 -TPBQ, which also agrees well with previous research. 46,49,50 In addition, to get insight for the increased QY in aggregate state after cyclization, we checked and compared the crystal packing of the two compounds ( Figure S27). Markedly, the arrangement of c 5 -TPBQ is relatively tight, forming a dimer-like packing, compared to the loosely packed o-TPBQ.…”
Section: Resultsmentioning
confidence: 99%
“…[ 7 ] Moreover, recent evidence demonstrated that several AIEgens shows aggregation‐induced ROS generation (AIROSG) effect, with 1 O 2 quantum yield of up to unity. [ 8 ] Thus, AIEgens afford great opportunities to fabricate highly efficient and activatable “turn on” photosensitizers for FL‐PDT.…”
Section: Introductionmentioning
confidence: 99%